Peningkatan Pengelolaan Infaq Baitul Maal BMT NU Singgahan Tuban melalui Program Ternak Kambing Bergulir - Moh. Muhajir; Lukman Khoirin (Universitas Muhammadiyah Surakarta, 2024)
Infaq from a financial management body or cooperative is generally channeled or used for social service activities. Likewise, at BMT NU Singgahan, the collected donations from members who have provided financing will be managed for social service activities or for donations to events that provide activity proposals to BMT NU Singgahan. Management of Baitul Maal BMT NU Singgahan infaq, which is still limited and underdeveloped, requires improvement in infaq management so that it can develop for the benefit of BMT NU Singgahan members and the surrounding areas. The aim of this community service program is to improve the management of Baitul Maal BMT NU Singgahan infaq through socialization and realization of the rolling goat program. The method used in this community service activity is the ABCD method (Asset based community development). This method is carried out by approaching the administrators and managers of BMT NU Singgahan and gathering information about existing programs. After that, a discussion was held regarding the BMT NU Singgahan infaq development program. As a result of the discussion, it was agreed that socialization of the rolling goat program could be carried out with resource persons from the Tuban Regency Livestock and Fisheries Service and goat farming practitioners. The socialization and realization of the rolling goat program was carried out with potential recipients of the rolling goat program and also the managers of the NU Singgahan BMT. The result of this community service activity is the realization of the rolling goat program for infaq management Baitul Maal BMT NU Singgahan with 4 program recipients and each received 3 breeding goats. The impact obtained by BMT NU Singgahan is that it can improve the management of Baitul Maal in generating profits for members. Meanwhile, the impact received by members can be helped by the existence of a business in the form of livestock. Monitoring and evaluation used in this program is by carrying out monthly control of livestock goats at the program recipient's residence and checking the condition of the livestock.